Effect of chemical fertilizers and microbial inoculations on soil properties in cassava (Manihot esculenta) growing Vertisols of Tamil Nadu - HRIDYA, A C; BYJU, G (The Indian Journal of Agricultural Sciences, 2014)
Cassava (Manihot esculenta Crantz) is an important subsidiary food and industrial raw material in the tropics. Considering the importance of the crop, an on farm experiment was conducted to study the effect of NPK fertilizer rate and biocontrol agents (Trichoderma and Pseudomonas fluorescens) and biofertilizers (Azospirillum, AM fungi and phosphorus solubilising bacteria) on soil chemical, biochemical and microbial biomass carbon in cassava growing Vertisols of Tamil Nadu during 2008 and 2009. The study was conducted in split plot design with two levels of NPK fertilizer as main plot treatments and eight microbial inoculations as subplot treatments. Azospirillum with Trichoderma (170.58 kg/ha), AM fungi with Trichoderma (57.85 kg/ha) and Trichoderma alone (473.70 kg/ha) significantly increased available nitrogen, phosphorus and exchangeable potassium by reducing the amount of NPK. Pseudomonas fluorescens with Trichoderma at 50 per cent recommended NPK rate increases the available iron in soil. The AM fungi with Trichoderma significantly increased available manganese and zinc compared to other inoculations at 50 per cent recommended NPK rate. Azospirillum with Trichoderma at the recommended NPK rate increased the urease enzyme activity (835.21 mg urea hydrolysed/g soil/h) compared to other treatments. The soil application of all cultures at 50 per cent recommended NPK rate increased soil dehydrogenase and b glucosidase enzyme activities. Interaction effect showed significantly higher microbial biomass carbon in AM fungi with Trichoderma at 50 per cent recommended NPK rate (3792.45 µg/g soil) and was on par with soil application of all cultures at 100 per cent and 50 per cent recommended rate. In general microbial inoculations at 50 per cent recommended rate gave on par or significantly higher results compared to uninoculated control at recommended NPK rate.